Սուրբ Ներսէս Շնորհալու երաժշտական ժառանգութիւնը - Վարդումեան, Արփի (տպ. Atlas)
The well-known 12th century Catholicos of Cilician Armenia, St. Nerses Shnorhali (The Graceful, 1100-1173), was one of the greatest persons of medieval Armenian culture and a talented poet-composer. His versatile artistic heritage belongs not only to the Armenian people, but also to the entire civilized world. St. Nerses the Graceful was not only an outstanding Armenian composer of his time, but also a great reformer of medieval Armenian musical thinking. He streamlined and renewed the old ceremony of the Armenian Church’s rite through his new and splendid creations. In addition, he edited nearly the whole musical heritage of previous composers and became the greatest reformer of Armenian spiritual music. The poetical and musical heritage of the eminent philosopher, composer and singer St. Nerses Shnorhali is extremely important in the history of Christian musical culture as a whole due to its content and depth. In his best creations St. Nerses Shnorhali predetermined European Renaissance tendencies in the developmental trends of medieval philosophical and aesthetic thought.
Keywords: Երաժշտութիւն; Արուեստ